Prevalence of negative emotional eating and its associated psychosocial factors among urban Chinese undergraduates in Hong Kong: a cross-sectional study - Katherine Y. P. Sze; Eric K. P. Lee; Rufina H. W. Chan; Jean H. Kim (BMC, 2021)
Abstract Background Emotional eating (EE), defined as eating in response to a range of emotions, has been previously associated with poor diet and obesity. Since there are limited data from non-Western populations, this study aims to examine the prevalence and factors associated with EE among urban Chinese university students. Methods A cross-sectional study was conducted on 424 university students (aged 18-24 years) from two large universities in Hong Kong in 2019. Respondents completed an anonymous online questionnaire that contained background questions, an emotional eating subscale of the Dutch Eating Behaviour Questionnaire (DEBQ), and Depression Anxiety and Stress Scales (DASS-21). Two-sample independent t-test and multiple regression analyses were conducted to test the association of study variables with negative emotional eating. Results There was over a three-fold higher likelihood of negative EE among females (14.8%) when compared with their male counterparts (4.5%) (OR = 3.7, p < 0.05). Having at least mild depressive symptoms was the only independent factor associated with negative EE among males (OR = 10.1) while for females, negative EE was independently associated with not having a romantic partner (OR = 3.45), having depressive symptoms (OR = 44.5), and having at least mild stress (OR = 5.65). Anxiety levels were not independently associated with negative EE for either gender. Both male and female students with negative EE had significantly lower self-perceived health scores, higher body mass index, and lower life satisfaction scores. Conclusions This study revealed that negative EE is prevalent among female Chinese university students and not uncommon among male students. Management of negative EE should be included as a component of university mental health promotion programmes in the region.